Locating emergency calls. (American City & County, 2004)
Focuses on the software upgrade done by the Downey Police Department's Communication Center in California, complying with Phase II Wireless E911 mandates, in October 2004. Mandate from the Federal Communications Commission; Information on the upgraded Downey public safety answering point system.